Artificial Intelligence in English as a Foreign Language: Opportunities and Challenges Faced by Islamic Tertiary Institutions - Renggi Vrika; Meli Fauziah (Universitas Islam Negeri Palopo, 2025)
Artificial Intelligence (AI) has become a disruptive force in the world of education, especially in the context of learning English as a Foreign Language (EFL). This study aims to identify opportunities and challenges in the use of AI-based tools in EFL learning in Islamic Tertiary Institutions. A descriptive qualitative approach was used by involving 30 students and 10 lecturers from various Islamic Tertiary Institutions in Indonesia. Data were collected through semi-structured interviews and analyzed using thematic techniques. The results of the study show that AI can give instant feedback and can be an academic writing support in general. However, there are challenges in the form of ethical issues, related to academic integrity and over-reliance on AI, institutional readiness, including data security, and limited digital pedagogical training as well. This study concludes that even AI integration has great potential in creating more inclusive and creative language learning in the digital era, it requires clear ethical guidelines, lecturer capacity building, and institutional policies aligned with Islamic educational values.